2021
DOI: 10.1155/2021/7207692
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins: Potential Therapeutic Targets for Defense against Oxidative Stress in Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is one of the most incapacitating neurological disorders. It involves complex pathological processes that include a primary injury and a secondary injury phase, or a delayed stage, which follows the primary injury and contributes to the aggravation of the SCI pathology. Oxidative stress, a key pathophysiological event after SCI, contributes to a cascade of inflammation, excitotoxicity, neuronal and glial apoptosis, and other processes during the secondary injury phase. In recent years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 155 publications
(225 reference statements)
1
22
0
Order By: Relevance
“…The secondary injury progression occurs not only at the site of impact, but it spreads along the entire spinal cord, including the faraway segments of the spinal cord that are not impacted, making the condition more devastating and debilitating with time [ 101 ]. Following injury, the elevated levels of ROS and the consequent oxidative stress are considered critical events associated with the secondary injury progression [ 102 ]. Under oxidative stress condition, dysfunctional mitochondria become the source of ROS [ 103 ] that cause a further cascade of degenerative processes, particularly curtailing ATP production required for normal cellular functioning, thus promoting apoptosis [ 103 ].…”
Section: Oxidative Stress and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The secondary injury progression occurs not only at the site of impact, but it spreads along the entire spinal cord, including the faraway segments of the spinal cord that are not impacted, making the condition more devastating and debilitating with time [ 101 ]. Following injury, the elevated levels of ROS and the consequent oxidative stress are considered critical events associated with the secondary injury progression [ 102 ]. Under oxidative stress condition, dysfunctional mitochondria become the source of ROS [ 103 ] that cause a further cascade of degenerative processes, particularly curtailing ATP production required for normal cellular functioning, thus promoting apoptosis [ 103 ].…”
Section: Oxidative Stress and Neurodegenerative Diseasesmentioning
confidence: 99%
“…NF‐κB, a member of the NF‐κB/Rel protein family, is a fast‐inducing transcription factor. In the acute phase of inflammation, mitochondria produce excess reactive oxygen species (ROS) that further activate NF‐κB to induce the expression of proinflammatory mediators, aggravating the inflammatory response and resulting in damage to the organism 66,67 . Excessive ROS‐mediated oxidative stress aggravates pain by activating the NF‐κB pathway 68,69 .…”
Section: Sirt1 and Neuropathic Painmentioning
confidence: 99%
“…In the acute phase of inflammation, mitochondria produce excess reactive oxygen species (ROS) that further activate NF-κB to induce the expression of proinflammatory mediators, aggravating the inflammatory response and resulting in damage to the organism. 66,67 Excessive ROS-mediated oxidative stress aggravates pain by activating the NF-κB pathway. 68,69 SIRT1 inhibits the NF-κB signaling pathway by deacetylating p65, a subunit of NF-κB, thereby alleviating inflammatory responses and oxidative stress.…”
Section: Sirt1 and Peripheral Nerve Injurymentioning
confidence: 99%
“…It consists of a series of auto-destructive cellular and molecular changes, such as inflammatory response, glial scar formation, edema, thrombosis, free radical release, and apoptotic and necrotic cells death. 10 , 11 Among the mechanisms of secondary injury, a robust and chronic inflammatory response has been observed at the injury epicenter and in surrounding areas. 12 , 13 Studies have demonstrated that this response can contribute to a wide range of inflammatory and autoimmune disorders that exacerbate lesion progression and hamper neurological function recovery.…”
Section: Introductionmentioning
confidence: 99%